TEACHERS’ PERCEPTION ON THE USE OF ENGLISH TEXTBOOKS IN TEACHING ENGLISH - Olivia Olivia (Universitas Jambi, 2020)
A learning process is a complex condition which needs consideration to make it goes well. So does the textbook being an important component that should be available in a school. Meanwhile textbook is the book of a certain subject that produced knowledge needs for the students which contained the materials of learning, the textbook also held a significant role in the learning process. The teachers as educators used textbooks to meet the needs of students learning targets and as the teaching advice in planning students’ activities in the classroom. Meanwhile, the student used textbooks as learning media in obtaining the updated information to help them enrich their ability of lesson subjects. Regarding the textbook issue, the researcher conducted the study of textbooks in teaching English at Junior High School in Jambi City by implemented a Qualitative descriptive approach in gaining the data. The technique used to gain the data was an interview. The data were analyzed descriptively. The respondent of the research was three English teachers who taught in each grade of students’ level. The results showed that the teachers perceived the textbook positively and it shows that the textbook used was not limited to the teachers to create another initial step to improve the students’ ability in understanding English even after considerin several minus aspects. The weakness of the main book makes the teacher uses other additional books in learning so that variety and sufficient material in the learning. Key word: Textbook, Textbook Used, Teachers’ Perceived